Effect of calcium-channel blockers on the risk of active tuberculosis and mortality: systematic review and meta-analysis - Meregildo-Rodriguez, Edinson Dante; Asmat-Rubio, Martha Genara; Bardales-Zuta, Victor Hugo; Vásquez-Tirado, Gustavo Adolfo (Frontiers in Pharmacology, 2024)
Recent studies suggest that calcium channel blockers (CCBs) could reduce the risk of active tuberculosis and improve clinical outcomes. We aimed to synthesize the evidence regarding the effect of CCBs on the risk of developing active tuberculosis and mortality.We systematically searched for observational studies and clinical trials published in six databases until August 31, 2023, following a PECO/PICO strategy.We included eight observational studies, 4,020,830 patients, among whom 241,761 had diabetes mellitus and 30,397 had active tuberculosis. According to our results, CCBs reduce the risk of developing active tuberculosis by 29% (RR 0.71; 95% CI 0.67-0.75) in patients with and without diabetes mellitus. However, CCBs do not show any benefit in terms of tuberculosis-related mortality (RR 1.00; 95% CI 0.98-1.02). For both outcomes, no statistical heterogeneity was found (I² = 0, p > 0.10). This protective effect of CCBs on the risk of active tuberculosis remained independent of the type of patient (with diabetes mellitus vs. general population) or the class of CCB administered (DHP-CCB vs. non-DHP-CCB) (test for subgroup differences I² = 0, p > 0.10). However, this beneficial effect was more significant among the general population (RR 0.70; 95% CI 0.66-0.74) compared to patients with diabetes mellitus (RR 0.72; 95% CI 0.61-0.86) and among those patients treated with DHP-CCBs (RR 0.69; 95% CI 0.63-0.74) compared to patients treated with non-DHP-CCBs (RR 0.72; 95% CI 0.67-0.78).CCBs may reduce the risk of active TB in patients with diabetes and the general population. On the contrary, CCBs do not have a protective effect on tuberculosis-related mortality. Furthermore, it may reduce the risk of mortality. However, more evidence is still needed. We recommend developing clinical trials to verify these findings, including more diverse populations.